alpha-Actinin-4 and the podocyte: Implications for focal segmental glomerulosclerosis - Michaud, Jean-Louis R (University of Ottawa (Canada), 2008)
Focal and segmental glomerulosclerosis (FSGS) is a common glomerular lesion and a significant cause of end-stage renal disease (ESRD). FSGS lesions result from damage to glomerular epithelial cells called podocytes, a key cell type involved in glomerular filtration. Mutations in the ACTN4 gene, encoding an actin-crosslinking protein, are causative of late-onset familial FSGS in humans. We have developed a mouse model of FSGS by expressing a high-affinity variant of alpha-actinin-4 (K256E) in a podocyte-specific manner. Transgenic mice display podocyte damage, subsequent loss of serum proteins into the urine (proteinuria), and glomerular sclerosis, similar to that observed in human patients. In cultured podocytes, alpha-actinin-4 K256E is mislocalized to stable actin-rich structures, which impairs cytoskeletal-dependent processes such as cell spreading and migration. We have also demonstrated that binding of alpha-actinin-4 to filamentous actin is regulated by calcium and phosphoinositides. Binding of calcium decreases the association of alpha-actinin-4 with actin, while binding of PIP2 and PIP3 enhances this interaction. High-affinity variants of alpha-actinin-4 are very static compared to the wildtype protein, and are insensitive to regulation by calcium or phosphoinositides. Such cytoskeletal dysfunction severely impairs the podocyte's ability to withstand mechanical stretch, a mimic of the distensive forces exerted on the podocytes in vivo. Although much insight has recently been gained into the biology of the podocyte, treatments for FSGS and other glomerular disorders remain few and ineffective. Further studies into the mechanisms involved in regulating the podocyte cytoskeleton in healthy and diseased states will surely lead to novel therapeutic interventions.
Keywords: Biology, Molecular.; Health Sciences, Medicine and Surgery.